Assessing Product Use Behavior and Exposure: Definitions and Methods - Yuki Dai; Giles Lesley; Scherer Max; Pluym Nikola; Ljung Tryggve; Mason Elizabeth; Newland Kirk; Chrea Christelle; Djoko Donatian Tafin; MaKena Patrudu; Cahours Xavier; Prasad Krishna (Contributions to Tobacco and Nicotine Research)
In recent years, the tobacco- and/or nicotine-containing product (TNP) portfolio has expanded to include products such as e-vapor products, heated tobacco products, and nicotine pouches. Although scientific papers and regulatory requirements/recommendations related to the assessment of product use behavior and exposure to product use have been published for these novel TNPs, there is great diversity in the terminology used to characterize and assess these types of products. The aim of this paper is to define the terms and methods used for assessing product use behavior and exposure, with the objective to suggest a uniform application of terms used by scientists working in this field of research. This publication is the work product of a cross-industry work item commissioned by the Cooperation Centre for Scientific Research Relative to Tobacco (CORESTA) Product Use Behaviour and Biomarkers Subgroups.